2016
DOI: 10.1080/09540253.2016.1219700
|View full text |Cite
|
Sign up to set email alerts
|

In the making: constructing in-school pregnancy in Mozambique

Abstract: This article examines current in-school pregnancy policy in Mozambique, Decree 39/GM/2003, discussing how it discursively constructs in-school pregnancy as a problem, thereby raising the need to regulate its occurrence. Decree 39/GM/2003 indicates that pregnant schoolgirls should be transferred to night courses in order to complete their education. Although progressive in some respects, as it allows pregnant girls to remain in education, the Decree reflects a global tendency to see education and pregnancy as o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…In Mozambique, Decree 39/ GM/2003 has been initiated where pregnant schoolgirls are initiated on extra mural studies in order to complete their education. 100 This review showed that DRC has the highest pregnancy rate, estimated at 62%: this correlates with the country's high birth rate. DRC is the highest populated country in SADC region and the 3rd populated country in sub Saharan Africa with an estimated population of over 80 million people and a fertility rate of 6.1% per woman.…”
Section: Discussionmentioning
confidence: 96%
“…In Mozambique, Decree 39/ GM/2003 has been initiated where pregnant schoolgirls are initiated on extra mural studies in order to complete their education. 100 This review showed that DRC has the highest pregnancy rate, estimated at 62%: this correlates with the country's high birth rate. DRC is the highest populated country in SADC region and the 3rd populated country in sub Saharan Africa with an estimated population of over 80 million people and a fertility rate of 6.1% per woman.…”
Section: Discussionmentioning
confidence: 96%
“…By the second trimester during my second year of teaching, 11 students had dropped out, including 8 male students. My observations contradicted the general information about education in Mozambique, and Africa as a whole, that have reported girls with a higher dropout rate (Chazen, 2017;Salvi, 2018). Hence, my research questions were: a.…”
Section: Research Focuscontrasting
confidence: 59%
“…Since Sabie Secondary School does not offer night school, the boys are left with no choice but to drop out. Typically, research has focused on the girls' side of the unplanned pregnancies, but it has been shown that the situation affects the boys, as well (Salvi, 2018).…”
Section: Discussion Of Findings Why Boys Drop Outmentioning
confidence: 99%
See 2 more Smart Citations